Propriedades anti-inflamat??rias do laser de baixa intensidade ap??s o infarto do mioc??rdio: participa????o dos pept??deos vasoativos e citocinas no remodelamento card??aco - Manchini, Martha Trindade (2014)
Anti-inflammatory properties of low level laser therapy after myocardial infarction: vasoactive peptides and cytokines in cardiac remodeling. Myocardial infarction (MI) is a worldwide health problem affecting millions of people in the world. The repercussion post-MI effects can cause elevated morbidity and mortality in the worldwide. Therefore, myocardial infarction it is the aim of many research which study ventricular dysfunction, cardiac remodeling and progression to heart failure . The search for new therapeutic strategies aimed at reducing and / or improve all these aspects. Recently, the low lever laser therapy appears as a new non-pharmacological tool which could attenuated the infarcted myocardial into adverse cardiac remodeling after MI and even improved heart function and reduced infarct size. The aim of this study was to evaluate the effects of low-level laser therapy (LLLT) in experimental rats that underwent coronary artery occlusion . 82 Wistar rats were used which were divided into three groups: control group (Con = 14), infarcted group (MI = 28) and infarcted group + Laser ( MI + Laser = 30 ) . All animals were subjected to analysis by echocardiography after three days to determine myocardial infarct size and cardiac function. Subsequently , we analyzed protein expression (IL - 6 , TNF - ?? , CINC - 1 and IL - 10) and gene (IL - 6 and IL - 1??) of inflammatory cytokines, gene expression (ACE , ACE2 , kinin B1 and B2 and but receptor ) protein and expression of receptor mas. We also analyzed the gene expression of apoptotic factors (Bax and Bcl - 2) and cardiotrophin - 1 . The results were reduced infarct size in MI+Laser group (34 ?? 2.6) when compared with MI group (42 ?? 2.7); IM + Laser group studied showed improved in fractional shortening (35 ?? 1) when compared to MI group (27 ?? 2). Furthermore, others functional parameters analyzed weren t significant between groups. In addition, the ACE -2 mRNA in MI + Laser increased after the LLLT when compared with MI (p ??? 0.05) and with receptor mas too (p ??? 0.05). Treatment with LLLT significantly increased the expression levels of kinins B2 receptor (p ??? 0.05) . Treatment with LLLT significantly increased the gene expression of Bcl - 2 in group IM + Laser compared with IM (p ??? 0.05), however no significant difference in gene expression of bax. The ratio of bcl2/bax suggests a lower activation of apoptotic processes after laser therapy. We found that after LLLT, IM + laser group showed higher gene expression of cardiotrophin 1 in relation to MI (p ??? 0.05). We conclude that functional parameters showed improvement after laser irradiation. Our data suggest that after irradiation, the laser decreases inflammation and facilitating cell survival post myocardial infarction, thus suggesting the contribution of the LLLT in adverse cardiac remodeling after MI.